Insights from the Plan Blue 21 game examining the role of sensing and partner and allied contributions to competition with Russia in the Arctic - Bartels, Elizabeth M.; Ochmanek, David A. 1951-; Edenfield, Nathaniel; Alkire, Brien (RAND, 2023)
Since 2016, Plan Blue wargames have explored scenarios that depict large-scale war fights against state adversaries in order to help U.S. Department of the Air Force (DAF) leaders better understand the demands of these potential war fights, evaluate the capabilities and limitations of programmed forces to meet those demands, and test new approaches to projecting power. The 2021 iteration of the game (Plan Blue 21) was set in the Arctic, in keeping with the Department of Defense's 2019 Arctic strategy, which calls for enhancing capabilities for operations in the region and strengthening the rules-based order there. The purpose of the game was to increase the DAF's understanding of the capabilities, posture, allied command, control, and communication relationships that may be called for to support future Arctic operations. Focusing on competition with Russia in the year 2030, game play took place in the context of steady-state competition and crisis operations rather than large-scale combat, and it explored the intersection of two key trends: (1) changing environmental conditions and (2) the completion of current Russian investments in new military capabilities and infrastructure in the Arctic. Plan Blue 21 was also specifically designed to test the extent to which capabilities for persistent and visible intelligence, surveillance, and reconnaissance can provide real-time situational awareness and potentially contribute to "deterrence by detection." U.S. players in Plan Blue 21 benefitted greatly from the participation of officers from key allied and partner countries that have important interests in and capabilities for operations in the Arctic region
Title from PDF document (title page; viewed December 15, 2023)
"RAND PROJECT AIR FORCE
"Prepared for the Department of the Air Force
Keywords: Prognose 2030; Kriegsspiel; Konflikt; Arktis; USA; Russland; United States / Air Force; Security, International / Arctic regions; Geopolitics / Arctic regions; Arctic regions / Strategic aspects; Arctic regions / Government policy / Russia (Federation); Geopolitical Strategic Competition; Russia; Security Cooperation; United States Air Force; États-Unis / Air Force; Géopolitique / Arctique; Arctique / Aspect stratégique; Arctique / Politique gouvernementale / Russie